Enhancement of Robust Image Hashing Technology through DWT-SVD - Jadhav Vishwajeet Narayanrao ,Vullanki Rajesh, (Journal of Computational Analysis and Applications (JoCAAA), 2024)
Robust image hashing is a critical technology in the field of digital image authentication,content-based image retrieval, and copyright protection. Unlike cryptographic hashing, whichproduces entirely different outputs for even minimal input changes, robust image hashing generates perceptually consistent hash values that remain stable across content-preservingtransformations while remaining sensitive to malicious tampering.